Cross-Cultural Education: Integrating Toraja Religion And Traditions In Building Social Harmony - Tekla Galla' Manase; Najamuddin; Alwi, Alimin (Cita konsultindo, 2026)
Abstract Cross-cultural education is a strategic approach in building an understanding of respect and tolerance towards cultural and religious differences in a multicultural society. This study aims to analyze how the integration of religion and traditions of the Toraja people can be a foundation for the formation of social harmony. Toraja as one of the regions in South Sulawesi, has unique characteristics with strong traditional traditions, such as Rambu Solo' and Rambu Tuka', which coexist with the dominance of Christianity, Catholicism, Islam and Aluk Todolo as a local belief system. This study uses descriptive qualitative with a literature study approach, documentation and narrative analysis, The results of the study show that the integration of religion and Toraja traditions through cross-cultural education can strengthen the values ​​of solidarity, mutual cooperation and respect for differences Cross-cultural practices are a concrete example of how education can act as a bridge to reduce the potential for identity conflict, while strengthening social cohesion. Thus. Cross-cultural education based on Toraja local wisdom is worthy of being implemented in the school curriculum and in community social activities.